2002
DOI: 10.1111/0272-4332.00062
|View full text |Cite
|
Sign up to set email alerts
|

The Media and Genetically Modified Foods: Evidence in Support of Social Amplification of Risk

Abstract: Empirical examinations of the "social amplification of risk" framework are rare, partly because of the difficulties in predicting when conditions likely to result in amplification effects will occur. This means that it is difficult to examine changes in risk perception that are contemporaneous with increases and/or decreases in social or media discussion of the risks associated with a particular risk event. However, the collection of attitude data before, during, and after the increased reporting of the risks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
213
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(234 citation statements)
references
References 20 publications
(20 reference statements)
12
213
3
2
Order By: Relevance
“…Studies have found a relationship between the volume of media reporting and people's perception of risk that is unrelated to the generalised level of trust in the media (Frewer, Miles, & Marsh, 2002;Frewer, Scholderer, & Bredahl, 2003;Vilella-Vila & Costa-Font 2008). Further, there is a convergence of the values of readers of elite press with media presentations over time (Bauer, 2005) Trust in the Australian food system differs from Europe.…”
Section: Trust In the Food Supplymentioning
confidence: 99%
“…Studies have found a relationship between the volume of media reporting and people's perception of risk that is unrelated to the generalised level of trust in the media (Frewer, Miles, & Marsh, 2002;Frewer, Scholderer, & Bredahl, 2003;Vilella-Vila & Costa-Font 2008). Further, there is a convergence of the values of readers of elite press with media presentations over time (Bauer, 2005) Trust in the Australian food system differs from Europe.…”
Section: Trust In the Food Supplymentioning
confidence: 99%
“…While this is not perfectly equivalent to individuals in crisis making decisions of when to seek care, we believe that the protocol used here, and in previous work (Cooper and Humphreys, 2008;Hall et al, 2010), provide a well-controlled environment in which to investigate infrequent and potentially high-risk health decisions, and examine perceptions of medical conditions. Notably, these results do not perfectly generalize to a patient population, an older or less educated population (Frewer et al, 2002), or individuals making health decisions on another's behalf (e.g., parents making health decisions about their child), this remains an important direction for future research. Additionally, this study was designed as a within-subjects study, with little opportunity to investigate the role of culture (e.g., Kirmayer, 1992), personal experience, nor familiarity with medical terminology.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work (Frewer et al, 2002) have found that perceptions of risk are more extreme in lay, older, and less educated populations, and responses are more likely to be heterogeneous within heterogeneous population. Given this study is an initial investigation into the impact of medical terminology on self-reported ratings of urgency, we opted to rely on a healthy undergraduate population in order to isolate, to the best of our ability, the influence of medical terminology on self-triage decision-making.…”
Section: Methods Participantsmentioning
confidence: 91%
“…Media coverage focuses on dramatic and rare events, such as nuclear accidents and natural disasters, to the exclusion of more common risks like smoking. Evidence shows that both the amount and the nature of media coverage are powerful predictors of public knowledge of events that amplify beliefs (Barabas and Jerit 2009;Nyhan and Reifler 2010), including risk assessments (Gore et al 2005;Frewer, Miles, and Marsh 2002). In other words, coverage amplifies observer risk assessments the more shocking and evocative it is, and the more plentiful it is.…”
Section: Disasters Personal Experience and The Mediamentioning
confidence: 99%
“…The first two deal with research design. First, the unpredictability of most LPHC events makes it challenging to carry out studies, and unethical to conduct most experiments, designed to explore amplification and numbing stimuli (Frewer, Miles, and Marsh 2002;Schlenger and Cohen Sliver 2006). Scholars cannot knowingly assign participants to treatments of disastrous conditions.…”
Section: Experiments and Disastersmentioning
confidence: 99%